Hubungan Emotional Quotient, Intelectual Quotient dan Spiritual Quotient dengan Entrepreneur’s Performance: Sebuah Studi Kasus Wirausaha Kecil di Yogyakarta - Muttaqiyathun, Ani (Universitas Prasetiya Mulya, 2009)
This study aimed to analyze the relationship and the influence of emotional, intellectual and spiritual quotient with the entrepreneur’s performance on the entrepreneurs in Yogyakarta. Pearson Product Moment Correlation and multiple regression analysis used to test the hypothesis in this study. Pearson Product Moment Correlation is used to test the relationship, F test was used to test the effect of independent variables on the entrepreneur’s performance and t-test was used to test the effect partially. The results of this study indicate that the entrepreneur’s performance was significantly related and influenced by emotional, intellectual and spiritual quotient simultaneously. The effect only partially occurs in emotional and intellectual quotient, while the spiritual quotient has no significant effect on the entrepreneur’s performance. In fact, the intellectual quotient has the most dominant influence on the entrepreneur’s performance.